2018
DOI: 10.1021/acsami.8b14125
|View full text |Cite
|
Sign up to set email alerts
|

User-Tailored Metal–Organic Frameworks as Supports for Carbonic Anhydrase

Abstract: Carbonic anhydrase (CA) was previously proposed as a green alternative for biomineralization of carbon dioxide (CO2). However, enzyme’s fragile nature when in synthetic environment significantly limits such industrial application. Herein, we hypothesized that CA immobilization onto flexible and hydrated “bridges” that ensure proton-transfer at their interfaces leads to improved activity and kinetic behavior and potentially increases enzyme’s feasibility for industrial implementation. Our hypothesis was formula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 71 publications
(164 reference statements)
2
54
0
Order By: Relevance
“…ZIF-8 was also chosen because previous preparation of thin films from this framework was shown to pose significant difficulties since the bulk material is usually made as brittle crystals or insoluble powders that are not amenable to common surface-processing techniques [ 38 , 39 ]. Above applications are also supported by known N 2 adsorption data, which showed that ZIF-8′s Brunauer–Emmett–Teller surface area was 1070.7 m 2 /g, while its Langmuir surface area was 1315.6 m 2 /g [ 40 ], both in the range of other supporting reports [ 41 ].…”
Section: Introductionsupporting
confidence: 65%
“…ZIF-8 was also chosen because previous preparation of thin films from this framework was shown to pose significant difficulties since the bulk material is usually made as brittle crystals or insoluble powders that are not amenable to common surface-processing techniques [ 38 , 39 ]. Above applications are also supported by known N 2 adsorption data, which showed that ZIF-8′s Brunauer–Emmett–Teller surface area was 1070.7 m 2 /g, while its Langmuir surface area was 1315.6 m 2 /g [ 40 ], both in the range of other supporting reports [ 41 ].…”
Section: Introductionsupporting
confidence: 65%
“…However, the poor stability and reusability of carbonic anhydrase limits its application in practice [6,8]. Enzyme immobilization on solid supports has been developed to overcome these shortcomings [9][10][11][12][13]. Previous immobilization studies mainly focused on commercial carbonic anhydrase on a wide range of solid supports such as: polyurethane foam [14], SBA-15 [15], mesoporous silica [16], MIL-160 [9] and ZIF-8 [17].…”
Section: Introductionmentioning
confidence: 99%
“…Enzyme immobilization on solid supports has been developed to overcome these shortcomings [9][10][11][12][13]. Previous immobilization studies mainly focused on commercial carbonic anhydrase on a wide range of solid supports such as: polyurethane foam [14], SBA-15 [15], mesoporous silica [16], MIL-160 [9] and ZIF-8 [17]. However, high cost and protracted immobilization processes greatly limit the application of immobilized CA [4,10,12].…”
Section: Introductionmentioning
confidence: 99%
“…Considering that such single-point assays also suffer from interference from reagents normally used in classical cellular approaches that could potentially influence MOF-induced toxicity assessment,25 we proposed to screen for cellular behavior upon exposure to MOFs of prevalent use by using only cell-based bio-sensorial approaches. To demonstrate the validity and applicability of the proposed approaches, we used MIL-160, a microporous hydrophilic aluminum-based MOF10,26 with a five-membered ring and an oxygen heteroatom,10 and ZIF-8, a hydrophobic framework of zeolitic imidazolate 10,27. Human bronchial epithelial (BEAS-2B) cells were employed as a pertinent model for toxicity assessment 28.…”
Section: Introductionmentioning
confidence: 99%
“…Human bronchial epithelial (BEAS-2B) cells were employed as a pertinent model for toxicity assessment 28. MOF selection was based on their demonstrated wide integration for gas storage applications,29 enzyme-based green technologies10 and drug delivery systems,30,31 while cell selection was based on demonstrated intrinsic sensitivity of such systems to convert biological activity into electrical measurements to be recorded in real time with an electric cell impedance sensing platform (ECIS) 25. By simply relying on the natural sensitivity of cells, our analysis demonstrates high-throughput, rapid and accurate screening and differentiation of toxicity based on MOFs physicochemical properties, as well as the capability for extension and large-scale screening of other MOF materials.…”
Section: Introductionmentioning
confidence: 99%